The Factors influencing the choice of satellite communication system in crisis management in Poland - Szachno, Artur (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The study presented in this article uses an approach that directs to the identification of key parameters supporting the selection of a mobile satellite communication subsystem as part of communication system for crisis management purposes. Crisis management is an important element of the process of returning to a stable state damaged by the impact of uncontrolled external factors. The parameters of mobile systems based on LTE communication in relation to the telecommunications infrastructure in Poland were compared with the possibility of using mobile satellite communication taking into account non-urbanized areas. In Poland, in accordance with the Crisis Management Act, there is a need to have a reliable crisis communication system that enables communication between the central command point, regional crisis management centers and poviat and municipal crisis management centers. Local centers operate based on digital services obtained from telecommunications operators and delivered to work stations at the permanent headquarters of officers involved in the crisis management process, as well as outside permanent locations to mobile control points in the area of the incident.